Statistical Analysis of Sales Growth and Capital Intensity in Tax Avoidance in the Consumer Non-Cyclicals Sector on the Indonesia Stock Exchange - Nirmala, Yeni; Nabila, D. Tialurra Della (PT FORMOSA CENDEKIA GLOBAL, 2025)
The consumer non-cyclicals sector refers to the primary goods sector that tends to have more stable performance even during economic recessions. This condition allows companies in this sector. The objective of this research is to investigate experimentally the partial and concurrent impacts sales growth and capital intensity on tax evasion. Using a sample of 150 businesses, the study takes a quantitative approach and applies multiple linear regression analysis using SPSS 26. The results of the research show that capital intensity has a positive and major impact on tax avoidance, sales growth has a negative and large impact on tax avoidance, and both sales growth and capital intensity have a significant impact on tax avoidance at the same time.